The Human-Tech Equation: Optimizing Performance in The Digital Workplace - Cecep Yoto Haryoto (Greenation International Journal of Economics and Accounting, 2023)
The purpose of this study is to find out and analyze: (1) Application of Information Technology (2) Competence; (3) Employee Performance and (3) Effect of Application of Information Technology and Competence on employee performance in the West Java Provincial Education Office, both simultaneously and partially. The research method used in this study was descriptive survey and explanatory survey, the unit of analysis in this study were employees in the Education Office of West Java Province with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the Application of Information Technology received by employees at the West Java Provincial Education Office was relatively adequate, the Competencies of Employees of the West Java Provincial Education Office were appropriate and sufficient to meet the needs, Employee Performance at the West Java Provincial Education Office was high, and The application of Information and Competence Technology simultaneously affects the Performance of Employees in the West Java Provincial Education Office. But Partially the Application of More Dominant Information Technology Affects Employee Performance rather than Competence. Because the Application of Information Technology is dominantly affecting performance, it is the first priority in improving employee performance. then the West Java Provincial Education Office is recommended to be given the appropriate Information Technology Application by increasing the ease of use of other information technology, so that they are able to work more professionally.